Coordination and Change - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2011)
The project will orient, align and integrate the four research for development projects (V1 -V4) that have been designed to respond to the basin development challenge in order to contribute to poverty reduction and improved livelihood resilience in the basin.